SISTEM PENGENDALIAN MANAJEMEN PERENCANAAN TERHADAP PRODUKTIVITAS KINERJA APARATUR DESA NUSANTARA JAYA KECAMATAN KERITANG INDRAGIRI HILIR - Ros Ningsih; Muhammad Fauzan; Yaswar Aprilian (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to determine the effect of management control system planning on the work productivity of village officials. The research method used is a quantitative approach with data collection techniques through questionnaires, interviews, and documentation. The research sample consists of village officials involved in carrying out village government duties. The data analysis technique employs simple linear regression using SPSS software. The results of the study indicate that the management control system planning has a positive and significant effect on the work productivity of village officials. This is evidenced by the regression coefficient value of 0.633, which indicates a positive relationship between the two variables. In addition, the results of the partial test (t-test) show a significance value of less than 0.05, meaning that the proposed hypothesis in this study is accepted. This indicates that the better the planning system implemented, the higher the work productivity of village officials. Thus, it can be concluded that management control system planning plays an important role in improving the work productivity of village officials. Therefore, it is necessary to enhance the quality of planning in a more directed and systematic manner to support the performance of village officials in providing public services.